Dynamic CRRT Prescription for Complicated Critically Ill Patient: A Case Report - Clemente Santorsola; Alberto Corona; Matteo Cecchi; Niccolò Castellani Nicolini; Elena Zendra; Alice Capone; Ivan Gatti; Matteo Brivio; Silvia Falsini; Gianluca Villa (Case Reports in Critical Care)
Continuous renal replacement therapies (CRRTs) and sequential extracorporeal blood purification (EBP) therapies can be used in patients with severe COVID-19 disease to support kidney failure and restore immune homeostasis. EBP prescription should be based on the patient’s clinical needs and frequently re-evaluated during the intensive care unit (ICU) stay. Personalization of treatment at the bedside plays a fundamental role for patient recovery. This aim can be simplified by using both clinical and molecular data collected from a patient-individualized web registry. In this case report, we describe how we apply a sequential approach to EBP therapies following the rapid evolution of a critically ill COVID-19 patient with acute kidney injury. We show patient strategies and outcomes using bedside data from a registry-based method for the routine use of EBP. We explain the choice of specific hemofilter prescription, also focusing on dose and anticoagulation strategies. We describe the difficulties, uncertainties, and mistakes made during EBP prescription. Furthermore, we discuss the causes and workable solutions that can be adopted by the ICU physician for a better EBP prescription, considering the current lack of well-recognized indications.